2017
DOI: 10.1530/rep-16-0674
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic DNA sensor-initiated innate immune responses in mouse ovarian granulosa cells

Abstract: Viral infections of the ovary may perturb ovarian functions. However, the mechanisms underlying innate immune responses in the ovary are poorly understood. The present study demonstrates that cytosolic viral DNA sensor signaling initiates the innate immune response in mouse ovarian granulosa cells and affects endocrine function. The cytosolic DNA sensors p204 and cGAS and their common signaling adaptor stimulator of interferon (IFN) genes (STING) were constitutively expressed in granulosa cells. Transfection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…S6c). In line with the previous report 35 , IRF3 deficiency significantly inhibited type I interferon and ISG expression, but had no effect on IL6 and TNFα expression ( Supplementary Fig. S6d, e).…”
supporting
confidence: 92%
“…S6c). In line with the previous report 35 , IRF3 deficiency significantly inhibited type I interferon and ISG expression, but had no effect on IL6 and TNFα expression ( Supplementary Fig. S6d, e).…”
supporting
confidence: 92%
“…Increased TNF‐α, IL‐6 and IL‐1β interfere with estradiol and inhibin synthesis . Our previous study demonstrated that increased TNF‐α in mouse ovary suppresses estradiol synthesis and induces antral follicle granulosa cell apoptosis through TNFR1 . The present study showed that human ovarian granulosa cells produced significantly high levels of TNF‐α, IL‐6 and IL‐1β in response to poly (I:C) treatment, whereas cytochrome aromatase (P450arom) and inhibin were dramatically decreased after poly (I:C) treatment.…”
Section: Discussionmentioning
confidence: 44%
“…Ovarian tissues were used for immunohistochemistry studies according to previously described procedures . Briefly, the fixed ovarian tissues were embedded in paraffin and cut into 5‐μm‐thick sections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations